Cytomegalovirus seropositivity is associated with increased arterial stiffness in patients with chronic kidney disease. - Nadezhda A Wall; Colin D Chue; Nicola C Edwards; Tanya Pankhurst; Lorraine Harper; Richard P Steeds; Sarah Lauder; Jonathan N Townend; Paul Moss; Charles J Ferro (PLoS ONE)
Background Patients with chronic kidney disease have an increased cardiovascular risk that is not fully explained by traditional risk factors but appears to be related to increased arterial stiffness. Cytomegalovirus (CMV) infection is associated with increased cardiovascular risk although the mechanisms for this are unknown. We examined whether CMV seropositivity was associated with increased arterial stiffness in patients with chronic kidney disease. Methodology and principal findings In 215 non-diabetic patients with chronic kidney disease, CMV seropositivity was determined using an anti-CMV IgG ELISA. Pulse wave velocity was measured and aortic distensibility assessed in the ascending, proximal descending and distal descending thoracic aorta. Patients seropositive for CMV had a higher pulse wave velocity and lower aortic distensibility at all 3 levels. These differences (except for ascending aortic distensibility) persisted in a subcohort matched for age, gender and renal function, and when the whole cohort was divided into quartiles of age. In multivariable analyses, CMV seropositivity was an independent determinant of pulse wave velocity and proximal and distal descending aortic distensibility. Conclusions In patients with chronic kidney disease, CMV seropositivity is associated with increased arterial stiffness and decreased distensibility of the proximal descending and distal aorta. These findings suggest that further research is required to examine CMV as a possible cause of arterial disease and increased cardiovascular risk in patients with CKD and may be relevant more widely for CMV seropositive patients with normal renal function.